2020
DOI: 10.1534/g3.120.401069
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Physiological Characterization of a Calcium Deficiency Phenotype in Maize

Abstract: Calcium (Ca) is an essential plant nutrient, required for signaling, cell wall fortification and growth and development. Calcium deficiency (Ca-deficiency) in maize causes leaf tip rot and a so-called “bull-whipping” or “buggy-whipping” phenotype. Seedlings of the maize line B73 displayed these Ca-deficiency-like symptoms when grown in the greenhouse with excess fertilizer during the winter months, while seedlings of the Mo17 maize line did not display these symptoms under the same conditions. These differenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 40 publications
0
8
0
1
Order By: Relevance
“…Ca is an essential mineral element for plant growth and development. Ca de cit symptoms have been described in various plants [21,22]. In this study, the seedlings of L. chinensis, the dominant forage grass in the eastern steppe of Eurasian continent, showed the Ca deprivation tolerant phenotype (Fig.…”
Section: Discussionmentioning
confidence: 50%
“…Ca is an essential mineral element for plant growth and development. Ca de cit symptoms have been described in various plants [21,22]. In this study, the seedlings of L. chinensis, the dominant forage grass in the eastern steppe of Eurasian continent, showed the Ca deprivation tolerant phenotype (Fig.…”
Section: Discussionmentioning
confidence: 50%
“…Bloom et al (2002) explain that a reducing rhizosphere pH resulting from N-NH 4 + uptake and a simultaneous extrusion of protons (H + ) by the root cells favors P uptake. In that sense, Kappes et al (2013) and Mateus et al (2020) also reported an increment in P concentrations in maize leaves in response to N rates, reinforcing the idea of synergism between N and P. Despite this beneficial effect for P, N supplied with sources containing a high proportion of N-NH 4 + , such as ammonium nitrate (50/50), by increasing this cation concentration in soil solution, may inhibit the uptake of other cations, such as Ca 2+ (Wang et al, 2020). However, for maize intercropping, the Urochloa plants could remove part of the NH 4 + applied at intermediate N rates, smoothing this cation inhibition over Ca 2+ , a contribution that stopped being significant when the highest N rate was applied.…”
Section: Crops Nutritional Statusmentioning
confidence: 86%
“…Despite this beneficial effect for P, N supplied with sources containing a high proportion of N–NH 4 + , such as ammonium nitrate (50/50), by increasing this cation concentration in soil solution, may inhibit the uptake of other cations, such as Ca 2+ (Wang et al., 2020). However, for maize intercropping, the Urochloa plants could remove part of the NH 4 + applied at intermediate N rates, smoothing this cation inhibition over Ca 2+ , a contribution that stopped being significant when the highest N rate was applied.…”
Section: Discussionmentioning
confidence: 99%
“…It is widely known that Ca 2+ is an essential plant nutrient [ 32 ]. Previous studies have shown that Ca 2+ deficiency can cause leaf-rot/wilting phenotype in Maize ( Zea mays L.) [ 33 ]. In cabbage ( Brassica oleracea L. var.…”
Section: Discussionmentioning
confidence: 99%